Observation of Type I Photonic Weyl Points in Optical Frequencies (Laser Photonics Rev. 12(2)/2018). Issue 2 (16th February 2018) - Goi, Elena; Yue, Zengji; Cumming, Benjamin P.; Gu, Min
Abstract : In article number 1700271, Min Gu and co‐workers fabricate optical type I Weyl points and demonstrate their chiral nature by coupling with spin‐angular momentum carried by circularly polarized light. This Weyl‐point induced mechanism leads to reversed circular dichroism along the directions that intersect the oppositely charged topological photonic states.